Knowledge, Perception, and Readiness of Indonesian Pharmacists for the Implementation of Telepharmacy-Based Pharmaceutical Services in Indonesia - Wathoni N; Lestari K; Iftinan GN; Rahayu SA; Nurlatifah A; Khairinisa MA; Elamin KM (Dove Medical Press, 2023)
Nasrul Wathoni,1 Keri Lestari,2 Ghina Nadhifah Iftinan,2 Susi Afrianti Rahayu,3 Anggun Nurlatifah,2 Miski Aghnia Khairinisa,2 Khaled M Elamin4 1Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 3Department of Pharmacy, Akademi Farmasi Bumi Siliwangi, Bandung, 40286, Indonesia; 4Graduate School of Pharmaceutical Sciences, Kumamoto University, Chuo-ku, Kumamoto, 862-0973, JapanCorrespondence: Nasrul Wathoni, Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM 21, Jatinangor, 45363, Indonesia, Tel/Fax +622 842 888888 3510, Email nasrul@unpad.ac.idBackground: Telepharmacy, a digital technology-driven approach, has emerged as a potential solution to address the challenges posed by this pandemic. Telepharmacy is a method used in pharmaceutical practice where a pharmacist utilizes telecommunications technology to supervise aspects of pharmacy operations or provide patient care services. This study aimed to assess pharmacists' level of knowledge, perception, and readiness toward telepharmacy in Indonesia.Methods: A cross-sectional approach was used in this study, and non-probabilistic purposive sampling technique was used to select respondents who were Indonesian pharmacists. The Telepharmacy Knowledge, Perception, and Readiness questionnaire, translated into Indonesian and administered online, was used to measure the pharmacist's knowledge, perception, and readiness level. Descriptive and inferential data analyses were performed using SPSS version 26, with a p-value of ≤ 0.05 considered statistically significant.Results: A total of 378 responses were obtained, with 96.83% exhibiting high knowledge and 63.23% showing high readiness for telepharmacy services. Furthermore, 58.20% of respondents had a positive perception of telepharmacy services. The results indicate a significant influence of pharmacist's knowledge and perception on their readiness to implement telepharmacy services in the future practice.Conclusion: Most study participants had sufficient knowledge, positive perceptions, and readiness to implement telepharmacy services in their future pharmaceutical practice. However, they expressed concerns about the potential for an increased workload and the potential lack of incentives associated with the widespread adoption of telepharmacy practice models. Telepharmacy practice models must be included in the training programs that train future's pharmacists in order to ensure that they have the abilities required to offer telepharmacy services.Keywords: telepharmacy, pharmacists, knowledge, perception, readiness, Indonesia